2023
DOI: 10.3389/fnins.2023.1308345
|View full text |Cite
|
Sign up to set email alerts
|

New insight on microglia activation in neurodegenerative diseases and therapeutics

Yucong Xu,
Wei Gao,
Yingnan Sun
et al.

Abstract: Microglia are immune cells within the central nervous system (CNS) closely linked to brain health and neurodegenerative diseases such as Alzheimer’s disease and Parkinson’s disease. In response to changes in the surrounding environment, microglia activate and change their state and function. Several factors, example for circadian rhythm disruption and the development of neurodegenerative diseases, influence microglia activation. In this review, we explore microglia’s function and the associated neural mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 202 publications
0
5
0
Order By: Relevance
“…In neurodegenerative diseases, microglial activation involves cellular metabolism dysregulation and mitochondrial damage, leading to the accumulation of reactive oxygen species (ROS), amino acids, iron, ferroptosis, and eventual inflammation and cell death [ 66 , 85 , 86 , 87 ]. Recently, it was revealed that circadian rhythm also plays a critical role in microglia activation and function and that the disruption of this rhythm can lead to neurodegenerative diseases [ 88 ].…”
Section: Microglia Synucleinopathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In neurodegenerative diseases, microglial activation involves cellular metabolism dysregulation and mitochondrial damage, leading to the accumulation of reactive oxygen species (ROS), amino acids, iron, ferroptosis, and eventual inflammation and cell death [ 66 , 85 , 86 , 87 ]. Recently, it was revealed that circadian rhythm also plays a critical role in microglia activation and function and that the disruption of this rhythm can lead to neurodegenerative diseases [ 88 ].…”
Section: Microglia Synucleinopathiesmentioning
confidence: 99%
“…Synucleinopathies are also considered a hallmark of dementia, including PD dementia (PDD) and Lewy body dementia (LBD), where the latter comprises roughly 20–30% of all dementia cases in the world and is considered the third most common form of dementia [ 88 , 89 ]. In Alzheimer’s disease (AD), co-morbid α-Syn pathology is present in up to 50% of cases.…”
Section: Microglia Synucleinopathiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurodegenerative diseases, microglial activation involves cellular metabolism dysregulation and mitochondrial damage, leading to accumulation of reactive oxygen species (ROS), amino acids, iron, ferroptosis and eventual inflammation and cell death [66,[85][86][87]. Recently, it was revealed that the circadian rhythm also plays a critical role in microglia activation and function and that disruption of this rhythm can lead to neurodegenerative diseases [88].…”
Section: Microglia-synucleinopathiesmentioning
confidence: 99%
“…Cell-to-cell transmission of α-Syn aligns well with the clinical course of the disease and is now considered the underlying mechanism for neurodegenerative diseases. What may cause α-Syn misfolding in the first place is believed to involve a combination of factors including aging, environmental factors, and exposure to toxins, which ultimately overwhelms the microglia's ability to maintain homeostasis and leads to neurodegeneration [88,89]. Aberrant circadian rhythmicity may also lead to extensive α-Syn aggregation [90].…”
Section: Microglia-synucleinopathiesmentioning
confidence: 99%